Expectation of Patients from Doctors - Absar, Md Nurul; Rahman, M Hamidur (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Doctors are produced to meet the health need of the people. People, as a patient have many expectations from a doctor. Doctors often don't know those expectations. The objective of this study was to find out the expectations of the patients from doctors and the goal is to make the doctors aware of these expectations so that they give due attention to those expectations. Waiting patients in GPs' clinic and the patients waiting in the out patient department of the Upozilla Health Complex and Rangpur Medical College Hospital were interviewed to know their expectation from doctors. Focus group discussion was done with community people to know their expectation from doctors when they need health care. It was found that most people expects good treatment (70.70%), greetings from doctor (51.91%), good history taking (100%), attentiveness (78.02%),to be allowed to narrate their ailments without interruption (87%), privacy (75%), clarification of prescription (75.15%), referral if needed (98%), dietary advice (67%), information about the ailment (75.79%), partnership in decision making (72.92%) and confidentiality (46.49%). DOI: 10.3329/jbcps.v26i1.4226 J Bangladesh Coll Phys Surg 2008; 26: 3-9